UV-C assisted microwave drying of Ashwagandha (Withania somnifera) leaves: Drying kinetics, fuzzy logic-based model evaluation, and selected optical and phytochemical attributes - Sudarshan Ramanathan; S. Samuel Nirmalsingh; P. Dinesh Kumar; Sumit Sudhir Pathak (Innovative Food Science & Emerging Technologies, 2026)

Diversity of naturalized plant species in a Ramsar-listed wetland complex of a mountain valley in the Nepal Himalaya - Hom Nath Pathak; Chitra Bahadur Baniya; Dinesh Raj Bhuju; Bharat Babu Shrestha (Journal of Mountain Science, 2026)

Green corrosion inhibition of mild steel in acidic media: electrochemical behavior and theoretical studies of Zingiber mioga essential oil - Lalrin Tluangi; Raj Kumar Mishra; Jay Prakash Rajan; Manisha Malviya; Raghvendu Pathak; Ashish Kumar Singh; Rashmi Sehrawat; Dinesh Kumar Sharma; Sunil Kumar Pandey; Bindu Mangla; Ved Prakash Singh (Environmental Science and Pollution Research, 2026)

Do microplastics play a role in the pathogenesis of neurodegenerative diseases? Shared pathophysiological pathways for Alzheimer’s and Parkinson’s disease - Alexander Chi Wang Siu; Keshav Raj Paudel; Gurjeet Singh; Gaurav Gupta; Sachin Kumar Singh; Dinesh Kumar Chellappan; Gabriele De Rubis; Suhrud Pathak; Brian Gregory George Oliver; Kamal Dua; Muralikrishnan Dhanasekaran (Molecular and Cellular Biochemistry, 2025)
The widespread presence of microplastics (MPs) in the environment has raised significant concerns about their potential impact on human health. As of 2023, the Ocean Conservancy estimates that adults may ingest up to 121,000 MPs annually. While the majority of these particles are cleared from the body, a small fraction can persist, as MPs are non-biodegradable and resist breakdown, posing long-term health risks that remain poorly understood. This review explores the emerging link between MP exposure and the development of neurodegenerative diseases, particularly Alzheimer’s disease (AD) and Parkinson’s disease [1]. MPs appear capable of triggering neurotoxic pathways, including activation of resident immune cells in the brain, oxidative stress, blood–brain barrier (BBB) disruption, mitochondrial dysfunction, and neuronal damage, which may contribute to neuroinflammation and disease progression. Specifically, six MP-related mechanistic pathways associated with AD were identified: BBB disruption, chronic inflammation, oxidative stress and ROS generation, mitochondrial dysfunction, impaired autophagy and proteostasis, and epigenetic alterations. Similarly, six pathways were implicated in PD: BBB disruption, oxidative stress in dopaminergic neurons, mitochondrial dysfunction, microglial-driven neuroinflammation, α-synuclein aggregation, and gut–brain axis [2] disruption. Ultimately, our findings underscore the urgent need for further research into the neurological consequences of chronic MP exposure in humans and highlight the importance of strengthening global policies to curb plastic pollution and mitigate its long-term health risks.

PEGylation-based surface engineering of islets with microparticles co-delivery for enhanced engraftment in streptozocin-induced hyperglycemic murine model - Prakash Shrestha; Shiva Pathak; Dinesh Chaudhary; Shobha Regmi; Manju Shrestha; Pawan Kumar Raut; Ju-Yeon Kim; Gorka Orive; Ha Rin Kim; Na Kyeong Lee; Seho Kweon; Jooho Park; et al. (Chemical Engineering Journal, 2025)

A review on supercapacitors: Development trends, challenges, and future perspectives - Iqbal Singh; Rohit Sharma; Amardeep kaur; Dinesh Pathak; Anupinder Singh; Muhammad Hamza; Mehtab Singh; Ajay Vasishth (Next Research, 2025)

Genetic Profiling of Spodoptera litura (Noctuidae: Lepidoptera) in Indian Sub-Tropical Sugar Beet - Santeshwari Srivastava; Varucha Misra; Arun Baitha; Himanshu Pandey; S. N. Sushil; M. Mohan; A. D. Pathak; Sangeeta Srivastava; Dinesh Singh; Ashutosh Kumar Mall (Sugar Tech, 2024)

Development of recombinant capsid protein-based single serum dilution ELISA for sero-detection of porcine circovirus type 2 infection in pigs - Ravishankara Yadhapura Venkatesh; Sohini Dey; Lukumoni Buragohain; Madhan Mohan Chellappa; Dinesh Chandra Pathak; Asmita Singh; Rudhreswaran Murugasamy; Vignesh Manivasagam; Nagendra Nath Barman (Veterinary Research Communications, 2024)

Development of antibody to virulence factor flagellin and its evaluation in screening Ralstonia pseudosolanacearum - Shalini Bhatt; S. Merwyn P. Raj; Neha Faridi; Dinesh Pathak; Ankur Agarwal; Shraddha P. Mishra (Brazilian Journal of Microbiology, 2024)

Insights into the mechanisms of diabetic wounds: pathophysiology, molecular targets, and treatment strategies through conventional and alternative therapies - Jagat Pal Yadav; Ankit Kumar Singh; Maria Grishina; Prateek Pathak; Amita Verma; Vikas Kumar; Pradeep Kumar; Dinesh Kumar Patel (Inflammopharmacology, 2024)

The impact of different fertiliser management options and cultivars on nitrogen use efficiency and yield for rice cropping in the Indo-Gangetic Plain: Two seasons of methane, nitrous oxide and ammonia emissions - Arti Bhatia; Nicholas J. Cowan; Julia Drewer; Ritu Tomer; Vinod Kumar; Shikha Sharma; Ankita Paul; Niveta Jain; Sandeep Kumar; Girish Jha; Renu Singh; Radha Prasanna; et al. (Agriculture, Ecosystems & Environment, 2023)

A hydroponic-based efficient hardening protocol for in vitro raised commercial kiwifruit (Actinidia deliciosa) - Sumit Purohit; Janhvi Mihra Rawat; Vivek Kumar Pathak; Dinesh Kumar Singh; Balwant Rawat (In Vitro Cellular & Developmental Biology - Plant, 2021)

Evaluation of a fusion gene-based DNA prime-protein boost vaccination strategy against Newcastle disease virus - Sagar A. Khulape; Hemanta Kumar Maity; Dinesh Chandra Pathak; Narayan Ramamurthy; Saravanan Ramakrishnan; Madhan Mohan Chellappa; Sohini Dey (Tropical Animal Health and Production, 2019)

Rescue of a recombinant Newcastle disease virus strain R2B expressing green fluorescent protein - Madhan Mohan Chellappa; Sohini Dey; Satish Gaikwad; Dinesh C. Pathak; Vikram N. Vakharia (Virus Genes, 2017)

Anti-inflammatory and chondroprotective effects of atorvastatin in a cartilage explant model of osteoarthritis - Nitya N. Pathak; Madhu C. Lingaraju; Venkanna Balaganur; Vinay Kant; Amar S. More; Dhirendra Kumar; Dinesh Kumar; Surendra K. Tandan (Inflammation Research, 2015)